1) (x+6)(x-1)
2) (x-5)(x-3)
3)(x-4)(x+3)
4)x-3)(x+2)
1) 1 - ( - 4) = 1 + 4 = 5;
2) 0 - ( - 7) = 0 + 7 = 7;
3) - 2.5 - 3.5 = - 6.
Во втором примере ответ: 3cosx+2sinx+c
а в первом я не поняла запись
Докажите тождество:
<u>а²+ав </u> :<u> ав(а+в) </u> : <u> а²+ав+в² </u> = (а+в)²
а²-в² а³-в³ а³в+3а²в²+3ав³+в⁴
1) <u>а²+ав </u> : <u>ав(а+в)</u> =<u> а(а+в) </u> : <u> ав(а+в) </u> =<u> а </u>* <u> (а-в)(а²+ав+в²) </u>=
а²-в² а³-в³ (а-в)(а+в) (а-в)(а²+ав+в²) а-в ав(а+в)
=<u>а²+ав+в²</u>
в(а+в)
2)<u> а²+ав+в² </u> : <u> а²+ав+в² </u> = <u>а²+ав+в² </u> * <u> в(а³+3а²в+3ав²+в³</u>) =
в(а+в) а³в+3а²в²+3ав³+в⁴ в(а+в) а²+ав+в²
=<u>а³+3а²в+3ав²+в³ </u>=(а+в)³ = (а+в)²
а+в а+в
(а+в)²=(а+в)²
Что и требовалось доказать.
((5 корень из 2 в квадрате) - 36) + 6 =
(25*2) - 30 = 20.